Variations in the Use of Racing Coil and Iridium Spark Plugs in Gasoline Engines, A Comparative Study - Oka Sandrio Putra; M Nasir (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
The increasing number of vehicles has resulted in an increase in air pollution. Innovations were made to improve engine performance and reduce levels of exhaust emissions. This research was conducted on several types of racing coil and iridium spark plugs which will be examined for their ability to reduce levels of exhaust emissions. Several types of racing coil and spark plug racing (iridium) are mounted on a gasoline motor and then tested and compared the exhaust emissions. The gasoline engine used is the Honda Supra X 125 motorcycle, the results of the study indicate the Blue Thunder coil and NGK Iridium are able to improve engine performance and reduce levels of exhaust emissions.